Routing performance of structured overlay in Distributed Hash Tables (DHT) for P2P - Rafiza Ruslan; Ayu Shaqirra Mohd Zailani; Nurul Hidayah Mohd Zukri; Nur Khairani Kamarudin; Shamsul Jamel Elias; R. Badlishah Ahmad (Institute of Advanced Engineering and Science, 2019)
This paper presents a routing performance analysis of structured P2P overlay network. Due to the rapid development and hectic life, sharing data wirelessly is essential. P2P allows participating peers move freely by joining and leaving the network at any convenience time. Therefore, it exists constraint when one measuring the network performance. Moreover, the design of structured overlay networks is fragmented and with various design. P2P networks need to have a reliable routing protocol. In order to analyse the routing performance, this work simulates three structured overlay protocols-Chord, Pastry and Kademlia using OMNeT++ with INET and OverSim module. The result shows that Pastry is the best among others with 100% routing efficiency. However, Kademlia leads with 12.76% and 18.78% better than Chord and Pastry in lookup hop count and lookup success latency respectively. Hence, Pastry and Kamelia architectures will have a better choice for implementing structured overlay P2P network.